2006
DOI: 10.1158/1055-9965.epi-05-0853
|View full text |Cite
|
Sign up to set email alerts
|

Is the Association between Cigarette Smoking and Breast Cancer Modified by Genotype? A Review of Epidemiologic Studies and Meta-analysis

Abstract: Epidemiologic studies have examined the association between cigarette smoking and breast cancer risk according to genotype with increasing frequency, commensurate with the growing awareness of the roles genes play in detoxifying or activating chemicals found in cigarette smoke and in preventing or repairing the damage caused by those compounds. To date, f50 epidemiologic studies have examined the association between smoking and breast cancer risk according to variation in genes related to carcinogen metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 83 publications
1
76
0
2
Order By: Relevance
“…The risk associated with smoking exposure may also vary according to genetic susceptibility, as found in a number of studies (reviewed by Terry and Goodman 42 , which indeed might explain part of the differences observed across EPIC , ever use of oral contraceptives (yes/non/missing), ever use of menopausal hormone therapy (yes/no/missing), menopausal status at baseline (premenopausal/postmenopausal/unknown), parity and age at first full-term pregnancy (nulliparous/parous and age at FFTP 25 years/parous and age at FFTP < 25 years/missing), age at menarche (<12/12/13/ 14 years), alcohol consumption (0/0-10/>10 g ethanol), physical activity (inactive, moderately inactive, moderately active, active, missing); in the assessment of smoking during a specific period, smoking during the other life periods was adjusted for. 3 Only among parous women.…”
Section: Epidemiologymentioning
confidence: 99%
“…The risk associated with smoking exposure may also vary according to genetic susceptibility, as found in a number of studies (reviewed by Terry and Goodman 42 , which indeed might explain part of the differences observed across EPIC , ever use of oral contraceptives (yes/non/missing), ever use of menopausal hormone therapy (yes/no/missing), menopausal status at baseline (premenopausal/postmenopausal/unknown), parity and age at first full-term pregnancy (nulliparous/parous and age at FFTP 25 years/parous and age at FFTP < 25 years/missing), age at menarche (<12/12/13/ 14 years), alcohol consumption (0/0-10/>10 g ethanol), physical activity (inactive, moderately inactive, moderately active, active, missing); in the assessment of smoking during a specific period, smoking during the other life periods was adjusted for. 3 Only among parous women.…”
Section: Epidemiologymentioning
confidence: 99%
“…Studies have examined genes that regulate metabolizing enzymes such as NAT2 and CYP1A1 [2,5,[8][9][10]. Other genes such as MnSOD have been examined because it may influence susceptibility to cigarette smoking because of their influence on oxidative stress [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Review of these studies show negative, positive or null association between smoking and breast malignancies (Palmer and Rosenberg, 1993;Hamajima et al, 2002;Fink and Lash, 2003). More recent studies suggest that smoking does not decrease but may enhance breast cancer risk depending upon the duration and frequency of smoking, age at the commencement of smoking and smoking before a first full-term pregnancy (Terry and Rohan, 2002;Gram et al, 2005;Terry and Goodman, 2006). Role of passive smoking in breast cancer has also been investigated and while some studies have found no association (Egan et al, 2002), others report a positive association between passive smoking and breast cancer risk (Morabia et al, 1996;Johnson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also examined if polymorphism of detoxifying, activating, or DNA damage-repair genes influence the breast cancer risk in smokers (Terry and Goodman, 2006). The results show either a positive or null association between long-term smoking and N-acetyltransferase (NAT-2), CYP1A1, glutathione S-transferase, sulfotransferase 1A1 genes (Terry and Goodman, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation